HYDRAULIC UNITS FOR DRIVING SYSTEMS OF RUNNING EQUIPMENT IN ROAD CONSTRUCTION MACHINERY - A. Ja. Kotlobai; A. A. Kotlobai; V. F. Tamelo (Наука и техника)
Operational efficiency of multi-functional road construction machines depends on number of working bodies which are simultaneously performing technological operations. Systems for propulsion pto to the running equipment drive and active working bodies of road construction machines are developing in the way of using three-axis hydraulic drives. When designing a hydraulic system for road construction machinery dividing of power flow from propulsion to the running equipment drive and active working bodies is considered as rather essential problem. Leading companies do not pay attention to the development of flow divider designs, preferring to produce more expensive multi-flow pumps. One of the ways to increase efficiency of multi-functional road construction machinery is an implementation of running equipment hydraulic driving system based on a mono-aggregate pump unit which consists of a pump and a volumetric divider of power fluid flow. A principle of volumetric division and summing-up of power fluid flows, technical realization and methodology for calculation of key parameters of discrete flow distributors has been developed on the basis of discrete hydraulics regulations. The paper presents results of mathematical modeling of hydraulic systems equipped with the discrete flow distributor. Analysis of a dual-motor hydraulic drive operation has shown the following results: a discrete flow distributor ensures independent load mode of the current consumer circuit operation from the load mode of the second consumer circuit within a wide range of loads; rational value of working fluid flow discretization parameter is the following value interval k = 4–6, maximum value of parameter efficiency is reached when an angular velocity of a distributor rotor coincides with the angular velocity of a pump shaft; discrete flow distributor provides a possibility to change parameters of hydraulic flow feeding in consumers’ pressure lines within a wide range due to changes in geometrical parameters of the design; discrete flow distributor should be installed either close to the pump or be integrated into its design. The developed mathematical model and methodology for determination of parameters for the discrete flow distributor allow to optimize its design. Application of the mono-aggregate pump unit which consists of a pump and a discrete flow distributor of running equipment drive in multi-functional road construction machinery permits to decrease a number of hydraulic drive pumps, to withdraw from large-sized and material-intensive pump drive gear box.